Verbal suggestions fail to modulate expectations about the effectiveness of a laboratory model of EMDR therapy: Results of two preregistered studies. (December 2021) - Mertens, Gaëtan; van Schie, Kevin; Lammertink, Sophie; Littel, Marianne; Engelhard, Iris M.
Abstract: Background and objectives: For many psychotherapies, like Eye Movement and Desensitization Reprocessing (EMDR) therapy, there is an ongoing discussion about the role of specific versus non-specific mechanisms in their effectiveness However, experimental research directly examining the potential role of non-specific mechanisms is scarce. Here, we address the role of a non-specific factor that is often put forward for EMDR, namely treatment effectiveness expectations, within a laboratory model of EMDR therapy. Methods: In a lab-based ( N  = 96) and an online experiment ( N  = 173), we gave participants verbal instructions to manipulate their treatment expectations. Instructions emphasized EMDR's effectiveness or ineffectiveness. Then, participants were asked to recollect an unpleasant autobiographical memory with or without making eye-movements. Results: In line with previous studies, we found significant reductions of reported vividness and emotionality of negative autobiographical memories in the eye-movements condition. These reductions did not differ between the verbal suggestions conditions in both experiments, suggesting a limited effect of treatment effectiveness suggestions. Limitations: Treatment effectiveness expectations were not successfully manipulated by the suggestions manipulation. This suggests that treatment expectations may be more difficult to influence than anticipated, thus limiting the interpretation of our findings. Conclusions: These findings tentatively corroborate the results of two earlier reports, suggesting that the effects of verbal suggestions about treatment effectiveness in a laboratory model of EMDR therapy may be limited. Highlights: Outcome expectations are thought to partly explain psychotherapy effectivity. Few studies have addressed this for EMDR therapy. We report result of two laboratory analogue studies (N = 96; N = 173). Treatment effectivity suggestions were not effective to change expectations. Intervention effects were not moderated by treatment effectivity suggestions.